Biofuels technology: A look forward - William Stafford; Adrian Lotter; Alan Brent; Graham von Maltitz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper assesses biofuels technology readiness and provides foresight to biofuels development in Southern Africa. Efficient conversion pathways, coupled with biomass from waste or high-yielding energy crops, reduces both the costs of biofuels production and the environmental impacts. Currently, most biofuels are more expensive than petroleum fuels and market uptake will be influenced by mandates and subsidies. Advanced biofuels promise greater efficiencies and carbon emission reductions at reduced cost, but will require further R&D to reach commercialization. If developed appropriately, biofuels can reduce carbon emissions and improve energy security, while enabling sustainable agriculture and improved natural resource management.
Keywords: O1; O2; O3; O5; Q1; Q2; 330; biofuels; bioenergy; technology maturity; technology readiness level; renewable energy; sustainable development